1110 The Cost of Fixing a Fractured Mandible: A Waste Reduction Project. (12th October 2021) - Mitchell, F; Parmar, J
Abstract: Introduction: Fractured mandibles are a frequent injury seen in the hospital and are commonly caused by interpersonal violence and accidental injury. The need to reduce expenditure in the NHS and redirect funds to where it is most needed is an important topic in recent times. The cost of open reduction internal fixation (ORIF) of mandible fractures can vary by the choice of equipment and technique used. Therefore, this waste reduction project aimed to identify any variation in treatment and minimise this. Method: A data collection exercise was performed of isolated mandibular fractures which required surgical intervention. Operation notes were examined from April 2018 to March 2019, with 99 cases found. Information was collected about the number and type of drill bits, plates and screws that were used in the surgery. The expected cost for plating different mandibular fractures including simple, comminuted and multiple fractures was calculated which was compared to the actual average cost by type of injury and operating surgeon. Results: The most common injury seen was Parasymphysis fractures, with the average ORIF cost across all surgeons being £239.07. The expected cost to fix this fracture was calculated at £237.95, or £325.31 if intra-operative intermaxillary fixation is used. It was demonstrated that the cost across all injuries was within the expected range and therefore no improvement could be made. Conclusions: By limiting the available equipment, stocking the most cost-effective options, and teaching surgeons standardised treatments we are able to reduce the cost and waste in the hospital.